Mechanisms of liver disease: the crosstalk between the NF-kappaB and JNK pathways. - Papa,S; Bubici,C; Zazzeroni,F; Franzoso,G (Biological Chemistry: official scientific journal of the GBM, 2009)
Abstract The liver plays a central role in the transformation and degradation of endogenous and exogenous chemicals, and in the removal of unwanted cells such as damaged, genetically mutated or virus-infected cells. Because of this function, the liver is susceptible to toxicity caused by the products generated during these natural occurrences. Hepatocyte death is the major feature of liver injury. In response to liver injury specific intracellular processes are initiated to maintain the liver integrity. Inflammatory cytokines including tumor necrosis factor (TNF)alpha and interleukin-6 (IL-6) are key mediators of these processes as they can activate different cellular response like proliferation, survival and death. TNFalpha induces specific signaling pathways in hepatocytes leading to the activation of either pro-survival mediators or effectors of cell death. While the activation of transcription factor NF-kappaB promotes survival, the induction of c-Jun N-terminal kinases (JNKs) and caspases represent the strategic effectors of cell death in the TNFalpha-mediated signaling pathway. This review summarizes recent advances in the mechanisms of TNFalpha-induced hepatotoxicity, suggesting that NF-kappaB plays a protective role against JNK-induced hepatocyte death. The identification of mechanisms regulating the interplay between the NF-kappaB and JNK pathways is required to identify novel targets for the treatment of liver disease, including hepatitis and hepatocellular carcinoma.